PROBLEMATIKA PELAKSANAAN EKSEKUSI PERKARA PERDATA DI PENGADILAN AGAMA (STUDI KASUS PENGADILAN AGAMA TANA LUWU) - Marwing, Anita; Mustaming, Mustaming (Al-Mizan (e-Journal), 2024)
This study aims to analyze the implementation of the execution of civil cases in the Religious Courts in Tana Luwu and the problems of its implementation, then provide solutions to the implementation of the execution of civil cases in the Religious Courts in Tana Luwu. This research is descriptive qualitative research. The results showed that: (1) Religious Courts in Tana Luwu have carried out executions based on incoming requests, but the number of requests for execution is very small, namely requests for execution of joint property cases as many as 7 cases and inheritance cases as many as 2 cases; (2) The inhibiting factors in the implementation of executions in Religious Courts in Tana Luwu, including Legal or regulatory problems, high case costs, lack of quantity and quality of human resources of the Religious Courts, and lack of public legal awareness; (3) Solutions offered in dealing with obstacles to the implementation of execution, namely: It is necessary to make a regulation of execution in the form of a guidebook to be used as a guideline in the implementation of execution, suspend the cost of execution, improve the quality of human resources of the judicial apparatus in the form of education and training.